Fluid-Shale Geochemical Characterization and Its Relation to Geomechanics: Implications for Low Recovery of Flowback Water during Hydraulic Fracturing in Shale Reservoirs - Zeng, Lingping (Curtin University, 2021)
This study aims to systematically reveal the role of fluid-rock interactions during hydraulic fracturing in shale reservoirs from both geochemical and geomechanical perspectives by conducting comprehensive physicochemical modelling with combination of spontaneous imbibition tests and rock mechanics experiments to understand the impact of fluid-rock interactions on shale wettability, water uptake ability, flowback water chemistry and geomechanical behaviours.